Analysis of Microplastic Content in the Digestive Tract of Clupeichthys goniognathus - Israk, Radiatun; Budijono, Budijono; Prianto, Eko (Faculty of Fisheries and Marine, Universitas Riau, 2025)
This research aims to determine the type and abundance of microplastics in the digestive tract of Clupeichthys goniognathus in the Koto Panjang Reservoir. This research was carried out from December 2023 – February 2024 in West Koto Tuo Village. Sampling was carried out by purposive sampling from the catch by fishermen. Sample analysis and microplastic identification were conducted at the Waste Processing Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The research results show that the microplastics identified in the digestive tract of C. goniognathus are fiber, film, and fragment types. The most common type found was film-type microplastics with an abundance of 35% or 119 particles